2001
DOI: 10.1007/pl00002381
|View full text |Cite
|
Sign up to set email alerts
|

p53 Levels, Cell Cycle Kinetics and Radiosensitivity in Two SV40 Transformed Wi38VA13 Fibroblast Strains

Abstract: These results suggest that 1. complex formation between the large T antigen and p53 reduces the latter's functionality; 2. in these two strains the G1 arrest is one of the factors determining radiosensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2002
2002
2003
2003

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…It is well accepted that p53 participates in the control of a cell cycle checkpoint before the cells enter S-phase [24]. Previous studies in our laboratory using the same cell lines as in the present study showed that entry into S-phase can be delayed only in the p53 wild-type cell lines, when the cells were irradiated in a quiescent state after 6-day culture in starvation medium [28].…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…It is well accepted that p53 participates in the control of a cell cycle checkpoint before the cells enter S-phase [24]. Previous studies in our laboratory using the same cell lines as in the present study showed that entry into S-phase can be delayed only in the p53 wild-type cell lines, when the cells were irradiated in a quiescent state after 6-day culture in starvation medium [28].…”
Section: Discussionmentioning
confidence: 45%
“…The status of p53 may be one of the important regulatory factors of cell cycle progression after irradiation [3,24]. It is well accepted that p53 participates in the control of a cell cycle checkpoint before the cells enter S-phase [24].…”
Section: Discussionmentioning
confidence: 99%
“…Facilitation and inhibition of metastasis may be both the possible consequences, but several other factors such as cellular phenotype, tissue type, the composition of extracellular matrix, cell cycle kinetics and radiosensitivity [28], radiation dose (fractionation) and time interval may play important roles. The present study shows that in colorectal tumor cells in vitro, integrins are changed in both a timeand dose-dependent manner after ionizing radiation and that the radiation-induced increase of adhesion to fibronectin and collagen is dependent on the 1 subunit of the investigated integrins.…”
Section: Discussionmentioning
confidence: 99%
“…An influence of different genetic alterations like TP 53 mutation, LOH10 and EGFR amplification on treatment response and recurrence is described in several trials [8,13,17,25,31,42]. Leenstra et al [27] demonstrated that patients with highgrade gliomas and genetic alterations like TP 53 mutation, complete LOH10 and EGFR amplification alone or in combination had a worse outcome than patients without genetic alterations.…”
Section: Clinical Relevancementioning
confidence: 99%